Determination of the residues of 9 kinds of antiviral drugs in animal-derived sports nutrition by HILIC-MS/MS - GUO Wei (Shipin yu jixie)
Objective: This study aimed to help with strengthening the monitoring of antiviral drug residues in animal-derived sports nutrition products. Methods: A method for determining the residues of 9 kinds of antiviral drugs in animal-derived sports nutrition was established, by using hydrophilic interaction chromatography tandem mass spectrometry. The samples were extracted by 1% acetic acid-acetonitrile and purified by PRiME HLB column. The mobile phase system of acetonitrile-10 mmol/L ammonium acetate solution (containing 0.1% formic acid) was separated by Sielc Obelisc R column in gradient elution mode to achieve the separation of nine target components. Results: The 9 kinds of antiviral drugs fractions had good linearity in the mass concentration range of 0.1~20.0 ng/mL, and the limit of detection was 0.1~0.5 μg/kg, with the limit of quantification of 0.3~1.5 μg/kg and the spiked recovery of 82.3%~95.7%, and the relative standard deviation was 3.2%~5.9% (n=5). Conclusion: The test method can meet the detection requirements of the residues of 9 kinds of antiviral drugs in the animal-derived sports nutrition.